Economic Value of Genetic Merit of Dairy Semen - Albert De Vries (EDIS, 2018)
Attempts to calculate the economic value of semen have been made since at least the 1970s. The basic calculations have since become available (Dechow 2016). This new 3-page fact sheet reviews these calculations, adds a few other considerations, and offers estimates of the worth of the genetics of dairy semen. Written by Albert De Vries, and published by the UF/IFAS Department of Animal Sciences, January 2018. http://edis.ifas.ufl.edu/an338